Proposta de modificação de um protocolo de avaliação da prontidão alimentar em recém-nascidos pré-termo - Gonçalves, Daniela da Silva (2021)
This study aimed to develop a short version of the POFRAS - Preterm Oral Feeding Readiness Scale by removing items found by previous studies to be less discriminative. We also evaluated the accuracy of the reduced instrument in the assessment of oral feeding readiness in premature neonates. An observational, retrospective database study was conducted on a sample of neonates evaluated using the POFRAS. The overall accuracy, sensitivity, specificity, and cutoffs for the short version of the POFRAS were determined using receiver operating characteristic curves. Data analysis involved descriptive methods, normality tests (Shapiro-Wilk tests), and comparisons (Student’s t-test or Mann-Whitney U tests) of individuals classified according to oral feeding readiness. Results were considered significant at p < 0.05. The cutoff for the POFRAS was set to 30 while that of the POFRASreduced was 19. The overall accuracy rates for the POFRAS and POFRAS-reduced were 69.23 and 69.89%, respectively. Both instruments classified a similar percentage of participants as “Not ready” (36.62%) and “Ready” (63.38%) for oral feeding. Preterm neonates classified as ready for oral feeding according to the POFRAS and POFRAS-reduced transitioned to full oral feeding approximately 5 days before the remainder of the sample. This difference was statistically significant. Neonates classified as ready for oral feeding were also discharged from the hospital approximately 4 days earlier than their peers, although this difference was not statistically significant. In conclusion, the removal of less discriminative items did not influence the accuracy of the instrument at assessing oral feeding readiness. The shorter duration of infant manipulation required by the POFRAS-reduced can also be considered an advantage over the original POFRAS.